Geomechanical Consequences of Large-scale Fluid Storage in the Utsira Formation in the North Sea. (November 2016) - Wangen, Magnus; Gasda, Sarah; Bjørnarå, Tore
Abstract: In this work we look at the geomechanical implications of injecting large volumes of fluid in the Utsira Formation. Our modelling is based on Biot's poroelasticity in combination with one-phase fluid flow. We study four different injection scenarios over 25 year: 1 Mt/year, 10 Mt/year, 100 Mt/year and 1000 Mt/year. We observe that the pore fluid pressure scales with the injection rate. The strain of the Utsira Formation and the related surface uplift can be estimated with simple a 1D model. A particular uncertainty with the modelling is the mechanical properties of the Utsira sand and the cap rock.